Connotation,service system of internet and its integrating path to manufacture - Juan DU; Feng WANG (Dianxin kexue)
After years of development,the internet continues to penetrate the economic and social fields and it has become an important infrastructure of information society,bringing increasingly influence and changes to the service industry,manufacturing industry and other traditional industries.The concept of“internet +”gradually gets into people's hearts.Internet service system was established based on analysis of connotation of internet,integrating path and its law to manufacture were researched systematically from industrial chain,value chain and enterprise production activities.